Safety profile of the 9-valent human papillomavirus vaccine: assessment in prior quadrivalent HPV vaccine recipients and in men 16 to 26 years of age. Issue 2 (1st February 2018) - Moreira, E. D.; Giuliano, A. R.; de Hoon, J.; Iversen, O.-E.; Joura, E. A.; Restrepo, J.; Van Damme, P.; Vandermeulen, C.; Ellison, M. C.; Krick, A.; Shields, C.; Heiles, B.; et al.
ABSTRACT: A 9-valent HPV (9vHPV) vaccine has been developed to protect against HPV type 6/11/16/18/31/33/45/52/58-related infection and disease. Previous safety analyses from 7 clinical trials conducted in 9vHPV vaccine recipients 9–26 years of age, including comparisons of 9vHPV and quadrivalent HPV (qHPV) vaccines in girls and women 16–26 years of age, showed that the 9vHPV vaccine was generally well tolerated. Additional safety analyses were conducted to include the results of new clinical studies. The safety profile of the 9vHPV vaccine in prior qHPV vaccine recipients (n = 3756 from 1 randomized controlled trial and 2 open-label extension studies) and young men (n = 248 9vHPV and n = 248 qHPV vaccine recipients from 1 randomized controlled trial) was evaluated. Vaccine was administered as a 3-dose regimen (at Day 1 and Months 2 and 6), and adverse events (AEs) were monitored. The most common AEs were injection-site events (91.1% and 79.0% in prior qHPV vaccine recipients and young men, respectively), the majority of which were mild. Discontinuations due to an AE were rare (0.2% and 0.0% among prior qHPV vaccine recipients and young men, respectively). In young men, the AE profile of the 9vHPV vaccine was generally similar to that of the qHPV vaccine. Overall, the 9vHPV vaccine was generally well tolerated in prior qHPV vaccine recipients and in young men, with an AE profile generally consistent with that previously reported with the broader clinical program.